2011
DOI: 10.1155/2011/297153
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of GABAergic Signaling in Autism Spectrum Disorders

Abstract: Autism spectrum disorders (ASDs) comprise a heterogeneous group of pathological conditions, mainly of genetic origin, characterized by stereotyped behavior, marked impairment in verbal and nonverbal communication, social skills, and cognition. Interestingly, in a small number of cases, ASDs are associated with single mutations in genes encoding for neuroligin-neurexin families. These are adhesion molecules which, by regulating transsynaptic signaling, contribute to maintain a proper excitatory/inhibitory (E/I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
207
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(222 citation statements)
references
References 114 publications
8
207
2
5
Order By: Relevance
“…During early development, GABA is an excitatory transmitter. A disturbance in GABAergic function at this stage causes neurodevelopmental disorders, such as mental retardation, Angelman syndrome, epilepsy, and autism (21). Recently, bumetanide has been shown to improve behavior in children with autism by reducing GABAergic excitation (22).…”
Section: Discussionmentioning
confidence: 99%
“…During early development, GABA is an excitatory transmitter. A disturbance in GABAergic function at this stage causes neurodevelopmental disorders, such as mental retardation, Angelman syndrome, epilepsy, and autism (21). Recently, bumetanide has been shown to improve behavior in children with autism by reducing GABAergic excitation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and genetic studies demonstrated that deficiencies in synapse function 1 are implicated in a wide range of brain disorders, including neurodegenerative 2 and psychiatric diseases such as schizophrenia 3,4 and autism. 5,6 A hallmark of synaptic specializations is their dependence on highly organized complexes of proteins that interact with each other. Therefore, the loss or modification of key synaptic proteins might directly affect the properties of such networks and, ultimately, synaptic function.…”
mentioning
confidence: 99%
“…GABA also is important in embryonic development, regulating a variety of developmental mechanisms. 8 The other duplicated genes in the region, COX7B2, ATP10D (mitochondrial proteins), COMMD8 (COMM domain containing 8), NFXL1 (zinc-finger protein), NIPAL1, CORIN (pro-ANP to ANP cleavage) CNG1 (cyclic nucleotide gated channel in retinal rod cells), TXK (tyrosine kinase regulating T-cell proliferation), TEC (tyrosine kinase important in osteoclastogenesis), are not involved in a central nervous system development and have not been previously identified as candidate genes in neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%